2015
DOI: 10.1186/s13633-015-0007-1
|View full text |Cite
|
Sign up to set email alerts
|

The pitfalls associated with urinary steroid metabolite ratios in children undergoing investigations for suspected disorders of steroid synthesis

Abstract: BackgroundUrinary steroid metabolite ratios may improve the diagnostic yield of potential disorders of steroid hormone synthesis.ObjectivesTo investigate the range of ratios and their predictive value in children with suspected disorders of steroid synthesis.Design and methodsTwelve ratios were calculated on steroid metabolite data analysed by gas chromatography–mass spectrometry in urine samples collected between 2008–2010 from 93 children. Urine samples were also analysed in 252 children with no known endocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 12 publications
0
20
1
Order By: Relevance
“…Using these cutoff values for detecting 5ARD2 patients (≥ 0.95) and carriers (≥ 0.99), the sensitivity and specificity of the urinary Et/An ratio for diagnosing patients were 67.57% and 86.2%, respectively, while for diagnosing carriers, the sensitivity was 67.92% and the specificity was 73.81%. These results were lower than those in other published studies (19,21,28). This discrepancy may have been caused by different study methods, the severity of the cases included, and lack of controls in the studies.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Using these cutoff values for detecting 5ARD2 patients (≥ 0.95) and carriers (≥ 0.99), the sensitivity and specificity of the urinary Et/An ratio for diagnosing patients were 67.57% and 86.2%, respectively, while for diagnosing carriers, the sensitivity was 67.92% and the specificity was 73.81%. These results were lower than those in other published studies (19,21,28). This discrepancy may have been caused by different study methods, the severity of the cases included, and lack of controls in the studies.…”
Section: Discussioncontrasting
confidence: 78%
“…Urinary steroid profiling (USP) is known to have a significant role in diagnosing several disorders affecting steroid metabolism, including congenital adrenal hyperplasia, Cushing syndrome, 17 beta-hydroxysteroid dehydrogenase, 3 beta-hydroxysteroid dehydrogenase, and 5 alpha-reductase type 2 deficiency (5,6,20,21). Chan et al (19) reported convincing results of USP using ratios of urinary 5β/5 steroid metabolites, including etiocholanolone/androsterone (Et/An), in detecting 15 cases of 5ARD2 and thereby, proposed the use of USP in the diagnostic algorithm of 5ARD2, replacing the use of the T/DHT ratio and molecular analysis.…”
Section: Introductionmentioning
confidence: 99%
“…These obstacles are likely to be overcome in the future, and NGS is likely to become the mainstay of investigations in diagnosis of DSD. Although, the majority of the respondents to this survey suggested that genetic testing should be targeted and based on history and biochemical characteristics, it was interesting to note that the majority of respondents believed that a genetic confirmation of a diagnosis was preferable to a biochemical confirmation when encountering a case of 5α reductase deficiency or 17βHSD3 deficiency, highlighting the shift towards molecular genetics and an appreciation of the lack of sensitivity in arbitrary metabolite ratios in diagnosing these conditions [2527]. …”
Section: Discussionmentioning
confidence: 99%
“…A moderate raise of 17OHP used to be considered as confirmation for non-classic congenital adrenal hyperplasia [46]. Nevertheless, biochemical analyses relying either on blood tests or 24 h urine collections do not always allow drawing indubitable conclusions [48][49][50]. Interpretation of the urinary steroid profiles is complex and requires lots of experience.…”
Section: Diagnostic Strategymentioning
confidence: 99%